Exploring the relationships between participatory decision-making, visit duration, and general practitioners' provision of argumentation to support their medical advice: Results from a content analysis. Issue 5 (May 2015) - Labrie, Nanon H.M.; Schulz, Peter J.
Highlights This paper describes a quantitative study of GPs' use of argumentation. It examines the relationship between argumentation and visit characteristics. GPs' argumentation is related to visit length and participatory decision-making. The overall number of arguments provided by the GP seems the key determinant. Argumentation may contribute toward achieving patient-centered communication.